2010
DOI: 10.1007/s10571-010-9584-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranins A and B as Regulators of Vesicle Cargo and Exocytosis

Abstract: Chromogranins (Cgs) are acidic proteins that have been implicated in several physiological processes such as vesicle sorting, the production of bioactive peptides and the accumulation of soluble species inside large dense core vesicles (LDCV). They constitute the main protein component in the vesicular matrix of LDCV. This latter characteristic of Cgs accounts for the ability of vesicles to concentrate catecholamines and Ca(2+). It is likely that Cgs are behind the delay in the neurotransmitter exit towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 57 publications
0
31
1
1
Order By: Relevance
“…The chromogranins are acidic proteins and are the most abundant components of secretory vesicles in the chromaffin cells (reviewed in Machado et al 2010;Bartolomucci et al 2003). The chromogranins bind catecholamines and calcium with high capacity and low affinity (Westermann et al 1988;Videen et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The chromogranins are acidic proteins and are the most abundant components of secretory vesicles in the chromaffin cells (reviewed in Machado et al 2010;Bartolomucci et al 2003). The chromogranins bind catecholamines and calcium with high capacity and low affinity (Westermann et al 1988;Videen et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Granins are found in endocrine and neuroendocrine cells from which they are co-released with monoamines during exocytosis [122,123]. In addition to regulating vesicular levels of transmitters, these proteins (or their proteolytic cleavage products) are implicated in dense-core vesicle formation, vesicular sequestration of Ca 2+ and modulation of exocytosis [122125]. …”
Section: Regulation Of Dopamine Releasementioning
confidence: 99%
“…To identify the molecular composition of secretory vesicles in different hippocampal interneuron subtypes, we started by characterizing the expression pattern of canonical LDCV markers CAPS-1 and chromogranin B (Speidel et al, 2003; Machado et al, 2010). According to previous work in primary cultured neurons (Farina et al, 2015), immunohistofluorescence analysis in adult mouse slices revealed high levels of CAPS-1 (Supplemental Figure 4) supporting the notion that this protein is associated with neuronal LDCVs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the chromogranin family (a.k.a. secretogranins) and CAPS have been found in both endocrine and neuronal tissue (Speidel et al, 2003; Machado et al, 2010; Bartolomucci et al, 2011). These findings pointed to the notion that despite the striking diversity of cargo, neuronal secretory vesicles may exhibit a fairly homogenous molecular composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation